Realitas Sosial Pengangguran Terdidik di Perkotaan: Studi Pada Lulusan Perguruan Tinggi di Rawamangun, Jakarta Timur - Hisyam, Ciek Julyati; Tuffahati, Fadia; Rahma, Intan Aulia; Fakhria, Itsna; Safaatun, Muharomah Ayu; Al-Fauziah, Rohmatul Amaliyah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Educated unemployment in urban areas is a paradox in human resource development in Indonesia. A bachelor’s degree that is expected to be a ticket to decent work does not guarantee easy access to the world of work. This study aims to understand the social reality of educated unemployment among college graduates in Rawamangun, East Jakarta. A qualitative approach with a case study method is used to explore the subjective meaning, social experiences, and survival strategies of individuals who experience unemployment. The social construction theory of Peter L. Berger and Thomas Luckmann is the main analytical framework in understanding how the status of “unemployed” is formed and negotiated in everyday life. The results of the study show that educated unemployment experiences social pressure, identity crisis, and dissonance between expectations and reality. The world of work that demands experience, technical skills, and personal connections is a major obstacle for new graduates. However, individuals are not passive: they form new meanings about work, get involved in family businesses, and maintain psychological stability through certain social strategies. This study shows that educated unemployment is not just an economic issue, but a social construction that has an impact on identity and social relations. Structural responses from education and employment systems are needed to bridge this gap.